Fatigue Life Analysis of Bogie Frame for Straddle Type Monorail Vehicle - 杜子学; 李吉慧; 朱兴高 (机车电传动)
In this paper, the structural strength analysis of bogie frame for straddle type monorail vehicle with the finite element method was provided. Based on the analysis results, combined with the material S-N curve and linear cumulative damage theory, the fatigue life of bogie frame was calculated, and the results showed that the strength and fatigue performance of bogie frame of monorail vehicle met the requirements.